Pueri and Pastoral Community in Virgil's Eclogues (ACME, 2024)
In Virgil’s Eclogues young people, who are massively present already in Theocritus, appear always alongside older people. The elders, or senes, are authoritative representatives of the pastoral community, often as repositories of an illustrious poetic tradition. The pueri are already poets, but they seek or receive full poetic acknowledgment from the community by the mouth of the seniores. This consecration is sometimes sealed by the delivery of the Pan flute and consequently of the poetic legacy of its previous possessor. It is a moment of passage in which the young becomes a fully-fledged member of the adult community and the heir of its bucolic tradition: in this way, the generational continuity ensures the continuity of the poetic tradition. While in the Aeneid the premature death of many pueri aspiring to appear like viri challenges the validity of this process, in the Eclogues the hope for continuity appears as the only way through which the community can pursue its own balance, albeit fragile.
Keywords: Virgil; Eclogues; Young and Elders; Pastoral Community; Poetic Succession; Generational Continuity